Enhancing student performance through smart classrooms / Zainuddin Ibrahim ... [et al.] - Ibrahim, Zainuddin; Arifin, Suriyani; Aliman, Sharifah; Mohd Salleh, Mohd Idzwan; Ramli, Ahmad Razi (UiTM Press, 2024)
This study aims to assess the efficacy of Smart Classrooms in enhancing teaching and learning at UiTM. A comparative analysis was conducted between students utilizing Smart Classrooms and those engaged in conventional learning settings across UiTM campusses. The study encompasses a total of 5046 students from various campuses. The results reveal a noteworthy disparity in the first semester, with students in Smart Classrooms achieving an average CGPA of 3.358, compared to 3.222 for conventional classrooms. Similarly, in the second semester, Smart Classroom students attained an average CGPA of 3.34, whereas conventional classrooms record an average of 3.217. However, the intricate nature of individual Smart Classrooms, incorporating diverse technologies, and the academic staff’s adoption of multifaceted teaching methods, driven by contemporary technological capabilities, warrant a more comprehensive investigation.